Youth's education for social entrepreneurship:outcomes and pitfalls of an applied project - Cordeiro, Cláudia (2020)
Nowadays the European Union’s social policy, in overall, advocates that society must lead efforts to overtake its problems by self-regulation. In coherence with such perspective, our research analyses the impact of a pioneer educational project aiming to create social value through the governance mentoring. Empowering citizens implies a priori to develop educational resources, boosting competences related to management and demystifying some pre-assumed myths about social economy.